The Impact of Behavioural Biases in Personal Banking: A Study on Sri Lankan Customers (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Behavioral finance shows that bias influences personal finance decisions. This study focuses on Sri Lankan customers during the turbulent economic situation in the country and the biases that come with it. It samples all present biases, loss aversion, anchoring, mental accounting, overconfidence, herding, status quo bias, and a further, valence-biased, psychologically motivated bias. A structured questionnaire with demographic, financial literacy, and behavioral-based banking questions, and behavioral bias on a Likert scale, was distributed to 400 personal banking customers selected through stratified random sampling, with 323 valid responses processed. Descriptive statistics, chi-square, independent samples t, and logit regression were the analytical methods used. Status quo bias and mental accounting were the leading ones with the highest mean scores. Present bias, overconfidence, and psychology bias significantly predicted the respondents reporting that their savings were always increasing. Bivariate tests also revealed age, education, and income association with gains in savings perception. Age and market condition attention were positive predictors of perceived success in savings, while higher present bias and emotion-driven tendencies were negative predictors. The study also shows strong dependence on fixed deposits, considerable use of online banking, and ongoing reliance on personal judgement and family advice when making financial decisions. The research offers the results of an under researched South Asian environment and recommends the creation of banking products with a perception of bias, the establishment of more comprehensible communication with the consumers, the creation of specific financial literacy programs, and the increased inclusion of digitally reluctant and low-income clients in the banking strategies.